Lower lymphocyte count is associated with increased risk of Parkinson's disease. Issue 6 (27th May 2022) - Jensen, Melanie; Jacobs, Benjamin; Dobson, Ruth; Bandres-Ciga, Sara; Blauwendraat, Cornelis; Schrag, Anette; Noyce, Alastair
Abstract : Objectives: Patients with established Parkinson's disease (PD) display differences in blood biomarkers of immune function, including leukocyte differentials, compared to controls. These may be useful biomarkers to predict PD and inform pathogenesis. We sought to identify whether peripheral immune dysregulation was associated with risk of subsequent PD. Methods: We examined the relationship between incident PD and baseline leukocyte differential count in UK Biobank, a longitudinal cohort with >500, 000 participants. We used a range of sensitivity analyses and Mendelian randomization (MR) to further explore the nature of associations. Results: After excluding individuals with comorbidities which could influence inflammation biomarkers, 465 incident PD cases and 312, 125 controls remained. Lower lymphocyte count was associated with increased risk of PD diagnosis (per 1-SD decrease in count OR 1.18, 95% CI 1.07–1.32, padjusted=0.01). The association between lower lymphocyte count and increased PD risk remained robust to sensitivity analyses. MR suggested that the effect of lower lymphocyte count on PD risk may be causal (per 1-SD decrease in lymphocyte count; ORMR 1.09, 95% CI 1.01–1.18, p=0.02). Conclusions: We provide converging evidence from observational analyses in UKB and MR that lower lymphocyte count is associated with an increased risk of subsequent PD. m.jensen@cantab.net